Маятниковые миграции в Циркумпонтийской степи и центральной Европе в эпоху палеометалла и проблема генезиса ямной культуры - Иванова, С.В.; Никитин, А.Г.; Киосак, Д.В. (Археологія і давня історія України, 2018)
Статья посвящена проблеме происхождения и распространения ямной культурно-исторической
общности (ЯКИО) в контексте недавно высказанной генетиками гипотезы о массовой миграции
популяционных групп, генетически связанных с
ЯКИО и несших в себе генетические детерминанты иранских неолитических земледельцев, охотников
и рыболовов северного Кавказа из Понто-Каспийской степи в центральную и северную Европу в начале бронзового века. This article is dedicated to the problem of the origin
and spread of the Yamna cultural-historical community
(YCHC) in the context of the hypothesis recently
expressed by geneticists about the massive migration
of population groups genetically related to YCHC and
carrying the genetic determinants of the Iranian Neolithic
agrarians and hunters and fishers of the North
Caucasus from the Ponto- Caspian steppe to central
and northern Europe at the beginning of the Bronze
Age. Based on an in-depth archeological and genetic
analysis, we propose that the genetic «invasion» of the Iranian-Caucasian genetic element into Europe at
the beginning of the Bronze Age, recently proposed by paleogenetisits on the basis of a large-scale study of
ancient DNA, was not the result of a large-scale migration of representatives of YCHC from the Ponto-
Caspian steppes to central and northern Europe, but the result of global population and cultural changes in
Eurasia at the end of the Atlantic climatic optimum. We further suggest that before the steppe genetics appeared
in Europe at the beginning of the Bronze Age, central European genetic determinants appeared in
the steppe in the Eneolithic, and that the movement of the steppe genetic element to Europe was at least in
part the second phase of the «pendular» migration of European expatriates, returning to the historical zone
of habitation. We also come to the conclusion that the very concept of distinguishing YCHC as a monolithic
entity is inappropriate, and that the groups of nomadic tribes of the Ponto-Caspian steppe most likely existed
as discrete communities, although united by a common ideology and a genetic relationship that included both
the Iranian-Caucasian (throughout the entire range), and European / Anatolian agricultural (locally) genetic elements.